Costa Rican marine gastropods: range extensions - Cruz, Rafael Al. (1996)
In this work five species of molluscs (Gastropoda) are reported for the first time from Costa Rica. The specimens were collected during the R.V. Victor Hensen Cruises. In the three study areas, beamtrawl and ottertrawl hauls were conducted along a depth gradient from about 20 m to 200 m. (Wolff and Vargas 1994). All specimens were preserved in 10% formalin and identified using Keen (1971). Notes about synonyms, size and geographic distribution are provided for each species based on Skoglund (1992).